Answer:
x = 5
Step-by-step explanation:
Given
f(x) = - 3x + 21 and f(x) = 6, then equating gives
- 3x + 21 = 6 ( subtract 21 from both sides )
- 3x = - 15 ( divide both sides by - 3 )
x = 5
Basically, it's saying make y=x by simplifying.
If you found this especially helpful, I'd appreciate if you'd vote me Brainliest for your answer. I want to be able to assist more users one-on-one!
The answer is B.
The mean is the average so, in this case, the average age of the voters. To get the average the person must take 100 random people who voted, as taking any others will not give them the average age.
Answer: 9x - 1 = 9(2) - 1 = 17
Step-by-step explanation:
m∠ABD = m∠ABC + m∠CBD
87 = 9x -1 + 6x + 58
87 = 15x + 57
30 = 15x
2 = x